Rural dairy technology - O'Connor, C.B. (International Livestock Research Institute, 1995)
This manual deals with milk processing in a rural and small-scale environment. It concentrates on traditional products or on products that are easily made, need little specialised equipment and can be easily adapted to the rural processing plant. Some background information in the areas of milk chemistry, dairy microbiology and milk and milk-product analysis is also given. Data presented include composition of milk of some species of mammal, average composition of cow milk, composition of lipids in whole bovine milk, principal fatty acids found in milk triglycerides, distribution of milk salts between the soluble and colloidal phases, stability of vitamins, bacterial types commonly associated with milk, effect of temperature on the growth of bacteria in milk produced under different conditions and manufacturing procedures for yoghurt, acidophilus milk and Kefir.